Clinical benefit of long-term use of dual antiplatelet therapy for acute myocardial infarction patients with the PEGASUS-TIMI 54 criteria - Lee, Kwan Yong; Hwang, Byung-Hee; Choo, Eun-Ho; Lim, Sungmin; Kim, Chan Jun; Kim, Jin-Jin; Byeon, Jaeho; Choi, Ik Jun; Oh, Gyu Chul; Choi, Yoon Seok; Yoo, Ki Dong; Chung, Wook Sung; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The optimal duration of dual antiplatelet therapy (DAPT) after 1 year of maintenance for acute myocardial (AMI) patients is not well known. We evaluated the effectiveness of extended DAPT usage after 2nd-generation drug elution stent implantation in AMI survivors who had no severe bleeding for 24 months. Methods: The primary ischemic endpoint was the risk of mortality, and the primary bleeding endpoint was the risk of BARC 3 or 5 (major) bleeding. We investigated the event rates 2 to 5 years after the index procedure. Results: Of 3382 post-AMI survivors who met the PEGASUS-TIMI 54 (PEGASUS) criteria and without major bleeding until 2 years, 2281 (67.4%) maintained DAPT over 24 months, and 1101 (32.5%) switched DAPT to a single antiplatelet agent. The >24 M DAPT group showed a lower risk of mortality than the 12 to 24 M DAPT group (7.2% vs. 9.2%; adjusted hazard ratio: 0.648; 95% confidence interval: 0.595-0.976; p <0.001). The mortality risk was significantly greater as the number of PEGASUS criteria increased (p <0.001). DAPT >24 months was not significantly associated with a decreased risk for major bleeding in the population meeting the PEGASUS criteria (2.0% vs. 1.1%; p=0.093). The results were consistent after propensity-score matching and inverse probability weighting to adjust for baseline differences. Conclusions: Extended DAPT over 24 months was associated with a lower risk of mortality without increasing the risk of major bleeding among two-year survivors after AMI who met the PEGASUS criteria and had no major bleeding events before 24 months.